SPION‐Decorated Nanofibers by RAFT‐Mediated Free Radical Emulsion Polymerization‐Induced Self Assembly. Issue 2 (10th September 2018) - Nguyen, Duc; Huynh, Vien; Pham, Nguyen; Pham, Binh; Serelis, Algirdas; Davey, Tim; Such, Chris; Hawkett, Brian
Abstract: RAFT‐mediated free‐radical emulsion polymerization is successfully used to synthesize polystyrene nanofibers using triblock amphiphilic macro‐RAFT copolymers as stabilizers. The polymerization is under RAFT control, producing various morphologies from spherical particles, nanofibers, nanoplatelets, and polymer vesicles. Optimum conditions are established for the synthesis of predominantly negatively charged polymer nanofibers. Superparamagnetic iron oxide nanoparticles (SPION)‐decorated nanofibers are formed by simple mixing of the SPIONs with the fibers at an appropriate pH. The composite material has been found to be superparamagnetic and could be aligned under a magnetic field. Abstract : SPION‐decorated polystyrene nanofibers with high iron oxide content are prepared by simple mixing of polymer nanofibers with iron oxide nanoparticles at appropriate pH. The nanofibers are synthesized by free‐radical emulsion polymerization self‐assembly (PISA) using our uniquely designed macro‐RAFT triblock copolymers as stabilizers. The decorated nanofibers display superparamagnetic properties and can be aligned in a magnetic field.